2022
DOI: 10.3390/biomedicines10123187
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Functional and Structural Changes in Patients with Spinal Muscular Atrophy—A Pilot Study

Abstract: Spinal muscular atrophy (SMA) is a rare, autosomal recessive neuromuscular disease. Recent years have seen a significant development of therapeutic options for SMA patients. With the development of treatment methods, it has become necessary to adapt a physiotherapeutic approach to the evolving clinical picture of SMA patients. We presented an analysis of 40 SMA patients undergoing pharmacological treatment, examined twice in an average interval of 5 months. Twelve patients (non-sitters) were evaluated using CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…On the other hand, these results differed from our previous publication, where an improvement of four points in the first part and a six point total score was shown at the 10-month follow-up [ 10 ]. However, that study also included young patients who were both diagnosed and received treatment relatively early, sometimes just after birth, and showed a surprisingly high improvement of nine and 13 points, which agreed with Pane’s assumption that patients show a significantly higher improvement in function in the first 12 months than at 24 [ 10 , 23 ]. Such an early diagnosis and treatment protected those children from both large-scale muscle loss and postural deformities.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…On the other hand, these results differed from our previous publication, where an improvement of four points in the first part and a six point total score was shown at the 10-month follow-up [ 10 ]. However, that study also included young patients who were both diagnosed and received treatment relatively early, sometimes just after birth, and showed a surprisingly high improvement of nine and 13 points, which agreed with Pane’s assumption that patients show a significantly higher improvement in function in the first 12 months than at 24 [ 10 , 23 ]. Such an early diagnosis and treatment protected those children from both large-scale muscle loss and postural deformities.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, we proved in our previous publication that SATR was negatively correlated with the HFMSE score. In this study, we observed older children in whom the structural changes did not progress as quickly as in younger children; also, some of them functioned relatively highly and therefore showed no improvement [ 4 , 10 ]. The structural parameter results also demonstrated that the shortening of one side (side trunk length difference) had a negative relationship with the RULM and the HFMSE total score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations